ALGUNAS CARÁCTERÍSTICAS LINGÜÍSTICAS DE LA OBRA MÉDICA DE ARETEO DE CAPADOCIA - Pérez Molina, Miguel E. (Myrtia, 1991)
In this article it is analyzed the Jonian dialect used by Aretaeus of Cappadocia in his medical work at the phonological and morphological level; it is also compared with tested data in Herodotus and the ’Corpus Hippocraticum’. Finally, there are studied some Attic characteristics and Homeric peculiarities.